2019
DOI: 10.29309/tpmj/2019.26.08.3301
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of umbilicus site port hernia after laparoscopic procedure.

Abstract: The objective of this study is to determine the frequency of umbilicus port site hernia after laparoscopic procedure. Study Design: Prospective study. Setting: Minimal Invasive Surgical Centre and General Surgery Department LUMHS Jamshoro. Period: March 2015 to February 2017. Materials and Methods: During these two years all the patients visiting surgery department for laparoscopic Procedure. All patients regardless of age and both were undergo base line investigation and preoperative anesthetics fitness done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…But laparoscopic surgery is not without risks. Studies (Abbasi et al 2019, Holihan et al 2016) have shown that patients undergoing a laparoscopic or a robotic procedure can be at risk of developing a port-site hernia (PSH). Although PSH is a fairly rare complication, for an estimated 0.2% to 4.8% of patients, it can be severe, and eventually require a reoperation and a small bowel resection due to strangulation and/or perforation of the bowel (Chennamsetty et al 2015, Damani et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…But laparoscopic surgery is not without risks. Studies (Abbasi et al 2019, Holihan et al 2016) have shown that patients undergoing a laparoscopic or a robotic procedure can be at risk of developing a port-site hernia (PSH). Although PSH is a fairly rare complication, for an estimated 0.2% to 4.8% of patients, it can be severe, and eventually require a reoperation and a small bowel resection due to strangulation and/or perforation of the bowel (Chennamsetty et al 2015, Damani et al 2020).…”
Section: Introductionmentioning
confidence: 99%